2023
DOI: 10.1155/2023/8298339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increasing Indoor Negative Air Ions on Cognitive Performance and Health of High Pure CO2 Level-Exposed College Students

Abstract: Cognitive performance is essential to foster learning. High CO2 concentrations are common in classrooms and can lead to reduced cognitive performance. Negative air ions (NAIs) can improve cognitive performance. This study explored the effects of indoor NAIs on the cognitive performance and health of college students exposed to a high pure CO2 environment. Forty college students were exposed to four sets of conditions (NAIs+500 ppm CO2, 500 ppm CO2, NAIs+2500 ppm CO2, and 2500 ppm CO2). Participants’ cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…2 As a result, excess CO 2 has greatly exacerbated the problem of environmental catastrophes such as global warming and sea level rise, 3,4 which has posed a threat to the global climate environment 5,6 and human health. 7,8 It has been shown that CO 2 exposure can affect cognitive abilities, 9 and is associated with increased mortality and hospitalization due to respiratory and cardiovascular diseases. 10 Therefore, CO 2 emissions and the massive consumption of fossil fuels are major challenges for the sustainable development of human society.…”
Section: Introductionmentioning
confidence: 99%
“…2 As a result, excess CO 2 has greatly exacerbated the problem of environmental catastrophes such as global warming and sea level rise, 3,4 which has posed a threat to the global climate environment 5,6 and human health. 7,8 It has been shown that CO 2 exposure can affect cognitive abilities, 9 and is associated with increased mortality and hospitalization due to respiratory and cardiovascular diseases. 10 Therefore, CO 2 emissions and the massive consumption of fossil fuels are major challenges for the sustainable development of human society.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have addressed improving ventilation in hospitals and clinics [21,22], schools [23][24][25], closed public spaces (e.g., libraries and malls) [26,27], laboratories [28][29][30], workplaces [31,32], and kitchens [33][34][35]. Ventilation systems for indoor spaces are used to improve the air quality of enclosed areas by removing particulate contaminations [36][37][38][39][40] and smoke [22,28,39,40], controlling humidity [41,42], dissipating heat [36,43], or a combination of all these applications.…”
Section: Introductionmentioning
confidence: 99%